2023
DOI: 10.18421/tem123-17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Computational and Critical Thinking Towards Modelling Competency Among Pre-Service Mathematics Teachers

Pavitra Kannadass,
Riyan Hidayat,
Pariang Sonang Siregar
et al.

Abstract: Participation in modelling activities significantly facilitates the development of mathematical skills. By utilizing the concept of mathematical modelling, students may be able to develop a more grounded understanding of mathematics. The objective of this research was to explore how computational thinking and critical thinking are connected to the mathematical modelling proficiency of pre-service teachers. Correlational quantitative research was conducted on 140 pre-service mathematics teachers from the Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Critical thinking skills, as essential skills for 21st century students ( Saiz and Rivas 2023 ), help students understand the transition between real-life situations and mathematics, and facilitate the design of unique problem-solving approaches. This implies that the stronger the critical thinking, the stronger the mathematical modeling skills ( Kannadass et al 2023 ). The above findings indicate that the higher the levels of mathematical metacognitive knowledge, metacognitive experience, and metacognitive monitoring among high school students, the stronger their critical thinking, leading to further enhancements of their mathematical modeling skills.…”
Section: Discussionmentioning
confidence: 99%
“…Critical thinking skills, as essential skills for 21st century students ( Saiz and Rivas 2023 ), help students understand the transition between real-life situations and mathematics, and facilitate the design of unique problem-solving approaches. This implies that the stronger the critical thinking, the stronger the mathematical modeling skills ( Kannadass et al 2023 ). The above findings indicate that the higher the levels of mathematical metacognitive knowledge, metacognitive experience, and metacognitive monitoring among high school students, the stronger their critical thinking, leading to further enhancements of their mathematical modeling skills.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significant correlations between computational thinking and critical thinking, as well as pre-service teachers' modeling skills, were reported in [12,13], where it was found that the fundamental concepts of CT promoted, organized, and structured English writing; increased students' writing motivation; and reduced their writing anxiety. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of technology and its corresponding media is a constant influence on the lives and existence of individuals (Hidayat & Wardat, 2023;Kannadass et al, 2023;Pellas et al, 2018). The dynamics of education have undergone a transformation, extending beyond conventional methods like whiteboards, textbooks, or papers.…”
Section: Introductionmentioning
confidence: 99%